2016
DOI: 10.1111/hir.12140
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐rater reliability of h‐index scores calculated by Web of Science and Scopus for clinical epidemiology scientists

Abstract: Our results showed a stronger relationship and increased agreement between raters when calculating the h-index of a scientist using Scopus compared to WoS. The higher inter-rater reliability and simple user interface used in Scopus may render it the more effective database when calculating the h-index of senior scientists in epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The data provided here contribute to the current bibliometric analysis literature by offering insight into the possible differences and similarities between major bibliometric databases in addition to a popular research social network's metrics. To our knowledge, this is the first description comparing the social networking site ResearchGate to other accepted databases; however, other work has similar correlations and differences when comparing Google Scholar, Scopus, and Web of Science in metrics such as H-index, citation growth rates, and number of citations for each paper per author [24][25][26][27]. Similarly to the findings described here, these previous studies have found that Google Scholar provides higher estimates of citation and publication counts, while Web of Science tends to produce significantly lower citation counts [18,24,28].…”
Section: Discussionmentioning
confidence: 80%
“…The data provided here contribute to the current bibliometric analysis literature by offering insight into the possible differences and similarities between major bibliometric databases in addition to a popular research social network's metrics. To our knowledge, this is the first description comparing the social networking site ResearchGate to other accepted databases; however, other work has similar correlations and differences when comparing Google Scholar, Scopus, and Web of Science in metrics such as H-index, citation growth rates, and number of citations for each paper per author [24][25][26][27]. Similarly to the findings described here, these previous studies have found that Google Scholar provides higher estimates of citation and publication counts, while Web of Science tends to produce significantly lower citation counts [18,24,28].…”
Section: Discussionmentioning
confidence: 80%
“…Our choice of the Web of Science was determined by data export capabilities of this tool. We would have preferred Scopus (Elsevier, Amsterdam, Netherlands) because of its efficient author identification algorithm ( 21 ). However, we encountered problems applying our methods to files obtained from Scopus.…”
Section: Discussionmentioning
confidence: 99%
“…Spearman's rank-order correlation was applied using SPSS, to evaluate the significant difference between the ranking of communication risk factors, identified in the SLR and quantitative analysis [116]. The correlation value of spearman's coefficient was found to be 0.460, that demonstrated that the ranking gathered from SLR and survey data were reasonably correlated.…”
Section: Comparison Of Slr and Empirical Studymentioning
confidence: 99%